The inhibitory effect of GsMTx4 on pain sensation during tooth movement in rats - WANG Ruofei, SHAO Lixin, LIU Xiaotong, ZHANG Miaomiao (Editorial Office of Stomatology, 2024)
Objective To investigate the inhibitory effect of GsMTx4 on pain sensation in rats during tooth movement, open field experiments and immunohistochemical staining by conducting. Methods Fifty-eight male SD rats aged 5-6 weeks were selected and a right maxillary tooth movement model was constructed. The rats were randomly divided into two groups: group A(control group) and group B(GsMTx4 group). They were also divided into 5 subgroups according to 4 h, 1 d, 3 d, 5 d, and 7 d. The left maxillary of the rats in group A was used as group C(blank control group). The open-field test was used to evaluate the pain level of rats. Immunohistochemical staining was used to observe the expression of nerve growth factor(NGF) and calcitonin gene-related peptide(CGRP) in periodontal tissues. Results At 4 h, 1 d, and 3 d, the total distance traveled by rats in group B within 5 minutes in the open-field was higher than that of group A (P<0.05). At 4 h and 1 d, the percentage of time in the center of rats in group B was higher than that in group A(P<0.05). The expressions of NGF and CGRP in groups A and B were higher than those in group C on 1 d, 3 d, 5 d, and 7 d(P<0.05). The expression of NGF and CGRP in group B were lower than those in group A at 4 h, 1 d, and 3 d(P<0.05). Conclusion GsMTx4 can inhibit the expression of NGF and CGRP during tooth movement and relieve the pain caused by tooth movement.